SOCIO-CULTURAL DEVELOPMENT OF THE SAKAI TRIBE COMMUNITY IN KESUMBO AMPAI VILLAGE, BATHIN SOLAPAN DISTRICT, BENGKALIS REGENCY (1995-2016) - Suroyo; Yuliantoro; nurulsuci (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The Sakai tribe is one of the isolated tribes in Indonesia, precisely in Bengkalis Regency, Riau Province. The Sakai tribe is divided into two parts, namely the Inner Sakai tribe and the Outer Sakai tribe. Sakai Dalam is a half-living Sakai resident living in the wilderness, with a livelihood hunting, fishing and retrieving forest products. Sakai luar are residents who inhabit villages adjacent to settlements of Malay tribes and other tribes. The development that occurs in the cultural aspect in the local wisdom of the Sakai Tribe in terms of Traditional Houses of course there are also developments in the social aspect. This study aims to find out the background, process of development and factors that affect the socio-culture of the Sakai tribe in Kesumbo Ampai Village, Bathin Solapan District, Bengkalis Regency (1995-2016). The method used in this study is a historical approach. With the results obtained, the socio-cultural development background of the Sakai tribe community in Kesumbo Ampai Village, Batin Solapan District was measured by aspects of social groups, culture, social institutions and social statistics. The process of socio-cultural development of the Sakai tribe in Kesumbo Ampai Village, Batin Solapan District is assessed on the social aspects of the community, education and culture of the traditional house of the Sakai tribe. The factors that affect the socio-cultural development of the Sakai traditional house in Kesumbo Ampai Village, Bathin Solapan District, Bengkalis Regency are influenced by internal factors and also external factors.